The Perception of Parents on Early Marriage Cases in Lapandewa Kaindea Village - Salmawati; Hastuti; Wa Nurfida (Penerbit Jurnal Indonesia, 2024)
The aim of this research is to understand how parents perceive early marriage cases in Lapandewa Kaindea Village and to determine the impact of these perceptions. The study uses social action theory and employs a qualitative research method with a descriptive qualitative data analysis approach, collecting data through observation and interviews. The informants consist of four people: parents whose children married at an early age, parents whose children did not marry at an early age, and a religious figure. The results show the perceptions of parents whose children did not marry early, the perceptions of parents about the causes of early marriage, and the perceptions of the religious figure. The factors contributing to early marriage in Lapandewa Kaindea Village include pregnancy outside of marriage, education, economic conditions, and communication factors. The impact of parents' perceptions on early marriage cases.